Crystallization and preliminary crystallographic analysis of SMase I, a sphingomyelinase from Loxosceles laeta spider venom - Zela, S. P.; Pedrosa, MFF; Murakami, M. T.; de Andrade, S. A.; Arni, R. K.; Tambourgi, D. V. (Blackwell Munksgaard, 2004)
SMase I, a 32 kDa sphingomyelinase found in Loxosceles laeta venom, is responsible for the major pathological effects of spider envenomation. This toxin has been cloned and functionally expressed as a fusion protein containing a 6 x His tag at its N-terminus to yield a 33 kDa protein [Fernandes-Pedrosa et al. (2002), Biochem. Biophys. Res. Commun. 298, 638 - 645]. The recombinant protein possesses all the biological properties ascribed to the whole L. laeta venom, including dermonecrotic and complement-dependent haemolytic activities. Dynamic light-scattering experiments conducted at 291 K demonstrate that the sample possesses a monomodal distribution, with a hydrodynamic radius of 3.57 nm. L. laeta SMase I was crystallized by the hanging-drop vapour-diffusion technique using the sparse-matrix method. Single crystals were obtained using a buffer solution consisting of 0.08 M HEPES and 0.9 M trisodium citrate, which was titrated to pH 7.5 using 0.25 M sodium hydroxide. Complete three-dimensional diffraction data were collected to 1.8 Angstrom at the Laboratorio Nacional de Luz Sincrotron (LNLS, Campinas, Brazil). The crystals belong to the hexagonal system ( space group P6(1) or P6(5)), with unit-cell parameters a = b = 140.6, c = 113.6 Angstrom. A search for heavy-atom derivatives has been initiated and elucidation of the crystal structure is currently in progress.